Intravenous thrombolysis for patients with reverse magnetic resonance angiography and diffusion‐weighted imaging mismatch: SAMURAI and NCVC rt‐PA Registries. (22nd November 2013) - Sakamoto, Y.; Koga, M.; Kimura, K.; Nagatsuka, K.; Okuda, S.; Kario, K.; Hasegawa, Y.; Okada, Y.; Yamagami, H.; Furui, E.; Nakagawara, J.; Shiokawa, Y.; et al.
<x xml:space="preserve">Abstract</x> Background and purpose The characteristics of reverse magnetic resonance angiography and diffusion‐weighted imaging (MRA‐DWI) mismatch (RMM), defined as a large DWI lesion in the absence of major artery occlusion (MAO), remain unknown, especially in patients treated with intravenous recombinant tissue plasminogen activator (rt‐PA). Methods Patients with stroke in the middle cerebral artery territory were included. Early ischaemic changes (EIC) were assessed with the Alberta Stroke Program Early CT Score on DWI (DWI‐ASPECTS). All patients were divided into four groups based on the presence of MAO and a DWI‐ASPECTS cut‐off value of <7. RMM was defined as DWI‐ASPECTS <7 without MAO. Clinical characteristics, symptomatic intracerebral hemorrhage (sICH) and favorable functional outcome (modified Rankin Scale score 0–2) at 90 days were compared amongst the four groups. Results Of the 486 patients enrolled (167 women, median age 74 years, median initial National Institutes of Health Stroke Scale score 13), reverse MRA‐DWI mismatch was observed in 24 (5%). Of the clinical characteristics, cardioembolism was the only factor that was independently associated with RMM [odds ratio (OR) 5.49, 95% confidence interval (CI) 1.25–24.1]. Multivariable analyses revealed that patients with RMM more commonly had sICH than those with DWI‐ASPECTS ≥ 7 irrespective of the presence (OR 5.44, 95% CI 1.13–26.1) or absence (13.1, 2.07–83.3) of MAO, and they had a more favorable functional outcome than those with DWI‐ASPECTS < 7 plus MAO (7.45, 2.39–23.2). Conclusion RMM was observed in 5% of patients treated with rt‐PA and associated with cardioembolism. Patients with RMM may benefit from thrombolysis compared with those with EIC with MAO, although increment in the rate of sICH is a concern.